The Impact Of Tiktok Live Information On Impulsive Buying Behavior - Wijaya, Azzahra Putri; Nurcahyani, Anastya; Dewi Kurniaty (Jurnal Ekonomi, 2024)
With its TikTok Live feature, TikTok has emerged as an influential platform shaping purchasing behavior. However, more research needs to be conducted that thoroughly examines the impact of TikTok Live information on impulsive buying behavior. This study aims to analyze the influence of TikTok Live information on impulsive buying behavior using a quantitative approach. Data were collected from 140 respondents through a purposive sampling technique. The study is grounded in the theory that TikTok Live is an interactive feature enabling real-time communication of product information to audiences, fostering consumer trust and engagement, which may trigger impulsive purchasing decisions. Impulsive buying refers to spontaneous purchasing decisions driven by emotions and various factors, such as brand loyalty, the desire to try new products, or being enticed by discounts. The findings reveal that the information conveyed through TikTok Live significantly negatively influences impulsive buying behavior. This suggests detailed TikTok Live information encourages rational consumer decision-making, reducing impulsive purchasing tendencies.